User Comments in Social Media Firestorms: A Mixed-Method Study of Purpose, Tone, and Motivation. Issue 3 (3rd July 2022) - Matook, Sabine; Dennis, Alan R.; Wang, Yazhu Maggie
ABSTRACT: Social media firestorms (SMF) are commonly seen as destructive forces of toxic comments hurled at a target for perceived wrongdoing. Yet some research suggests that SMF can provide beneficial outcomes for the target. In two studies, we qualitatively examine SMF comments (in terms of purpose and tone) and quantitatively examine users' motivations for making different types of comments. Results show that SMF comments are diverse, either supporting or condemning the target and being either aggressive or cordial in tone. Further, the results show that users' understanding of the triggering event in the real world influences the purpose of their comment (support or condemn) while disinhibition and others' online comments (i.e., herd influence) shape how they comment (tone). We conclude with an expanded SMF definition as " A digital artifact created by large numbers of user comments of multiple purposes (condemnation and support) and tones (aggressive and cordial) that appear rapidly and recede shortly after ". Some SMF persist as destructive and harmful firestorms; some exist to condemn the target but without aggressive language; and some support the target's behavior. Thus, SMF are not always abusive and toxic. The implications of our research are that SMF can be positive, enable collective actions, and require a detailed examination of their elements (purpose and tone) to understand their effects in the digital and real world.